Ketahanan Pernikahan pada Pasangan Commuter Marriage: Pemaknaan dan Praktik Kesabaran serta Kesyukuran: Marital Resilience in Commuter Marriages: The Meaning and Practice of Patience and Gratitude - Larasati Adiva Putri; Irsan Irsan (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
A commuter marriage is a phenomenon in which a married couple maintains a long-distance relationship due to work demands, thereby facing emotional, relational, and practical consequences. Despite these pressures, some couples are able to maintain the resilience of their marriage. This study aims to understand the experiences of couples in commuter marriages as they navigate marital resilience, as well as how they interpret and practice patience and gratitude in maintaining that resilience. This study employs a qualitative approach with a phenomenological design to explore the life experiences of couples in commuter marriages. Data were collected through open-ended questionnaires and in-depth interviews with 25 informants selected through purposive sampling, and were subsequently analyzed using thematic analysis. The results indicate that, first, couples in commuter marriages maintain marital resilience through commitment, communication, trust, and social support. Second, patience and gratitude are interpreted as spiritual attitudes manifested in acceptance of God’s will, emotional regulation, prayer, drawing closer to God, and behaviors that nurture the relationship. These two values support the maintenance of marital resilience as a foundation of strength, a practice of worship, a mechanism for satisfaction and acceptance, and a spiritual protective factor.